Anisotropy of thermal transport in phosphorene: a comparative first-principles study using different exchange–correlation functionals. Issue 12 (27th May 2022) - Zhang, Fa; Zheng, Xiong; Wang, Huimin; Ding, Liang; Qin, Guangzhao
Abstract : Using 12 different exchange–correlation functionals, the phonon transport properties of phosphorene are systematically studied by solving the Boltzmann transport equation. Abstract : Phosphorene, as a new type of two-dimensional (2D) semiconductor material, possesses unique physical and chemical properties, and thus has attracted widespread attention in recent years. With its increasing applications in nano/optoelectronics and thermoelectrics, a comprehensive study of its thermal transport properties is necessary. It has been concluded from previous studies that there exist vast differences and uncertainties in the theoretically predicted thermal conductivity, which is generally attributed to the selection of an XC functional. However, there is no comprehensive investigation on this issue. In this study, based on first-principles calculations using 12 different exchange–correlation (XC) functionals, the phonon transport properties of phosphorene are systematically studied by solving the Boltzmann transport equation (BTE). The results show noticeable differences in the phonon transport properties of phosphorene under different XC functionals. For instance, the thermal conductivity of phosphorene along the zigzag direction ranges from 0.51 to 30.48 W m −1 K −1, and that along the armchair direction ranges from 0.15 to 5.24 W m −1 K −1 . Moreover, the anisotropy of thermal conductivity is between 3.4 and 6.9, which fundamentally originates from the special hinge-like structure. This study conducts an in-depth analysis of phonon transport to reveal the effect and mechanism of different XC functionals in predicting the thermal transport properties, which would provide a reference for future research on phosphorene and other novel materials.